Germline APOBEC3B deletion is associated with breast cancer risk in an Asian multi-ethnic cohort and with immune cell presentation - Wen, WX; Soo, JS-S; Kwan, PY; Hong, E; Khang, TF; Mariapun, S; Lee, CS-M; Hasan, SN; Rajadurai, P; Yip, CH; Taib, NA; Teo, SH (BioMed Central, 2016)
Background: APOBEC3B is a cytosine deaminase implicated in immune response to viral infection, cancer predisposition and carcinogenesis. Germline APOBEC3B deletion is more common in East Asian women and confers a modest risk to breast cancer in both East Asian and Caucasian women. Analysis of tumour samples from women of European descent has shown that germline APOBEC3B deletion is associated with an increased propensity to develop somatic mutations and with an enrichment for immune response-related gene sets. However, this has not been examined in Asian tumour samples, where population differences in genetic and dietary factors may have an impact on the immune system. Methods: In this study, we determined the prevalence of germline APOBEC3B deletion and its association with breast cancer risk in a cross-sectional hospital-based Asian multi-ethnic cohort of 1451 cases and 1442 controls from Malaysia. We compared gene expression profiles of breast cancers arising from APOBEC3B deletion carriers and non-carriers using microarray analyses. Finally, we characterised the overall abundance of tumour-infiltrating immune cells in breast cancers from TCGA and METABRIC using ESTIMATE and relative frequency of 22 immune cell subsets in breast cancers from METABRIC using CIBERSORT. Results: The minor allelic frequency of APOBEC3B deletion was estimated to be 0.35, 0.42 and 0.16 in female populations of Chinese, Malay and Indian descent, respectively, and that germline APOBEC3B deletion was associated with breast cancer risk with odds ratios of 1.23 (95 % CI: [1.05, 1.44]) for one-copy deletion and 1.38 (95 % CI: [1.10, 1.74]) for two-copy deletion compared to women with no deletion. Germline APOBEC3B deletion was not associated with any clinicopathologic features or the expression of any APOBEC family members but was associated with immune response-related gene sets (FDR q values < 0.05). Analysis of breast cancers from METABRIC revealed breast cancers from APOBEC3B deletion carriers to have significantly higher abundance of tumour-infiltrating immune cells (P < 0.001). Conclusions: Taken together, our data suggests that tumour-infiltrating immune cells may be an important feature of breast cancers arising in women with APOBEC3B germline deletion, and that this may be of particular interest in Asian women where the germline deletion is more common.